A Christmas Homecoming - Perry, Anne (Headline Publishing Group, 2011)
In A Christmas Homecoming, a familiar face from the Charlotte and Thomas Pitt novels--Charlotte's mother, Caroline--travels with her young husband, Joshua Fielding, and his theatrical troupe to Whitby, the Yorkshire fishing village where Dracula the vampire first touched English soil in the sensational novel named after him. Joshua has arranged to produce a stage adaptation of Dracula by the daughter of Whitby millionaire Charles Netheridge during the Christmas holiday, but after the disastrous first read-through of her amateurish script, only the fact that the company is depending on Netheridge's financial backing for their spring tour keeps them at work. As tempers flare and wind and snow swirl around Netheridge's lonely hilltop mansion, a black-cloaked stranger emerges from the storm--an eerily opportune arrival, for this enigmatic figure, one Anton Ballin, turns out to be a theatrical genius. At the same time, a brooding evil makes itself felt. Instead of the theatrical triumph that Netheridge desired for his daughter, there is murder--shocking and terrifying.
Keywords: Christmas & Advent; Holidays & Celebrations; Juvenile Fiction